Role of TOPS score in predicting the prognosis of acutely ill children presenting to paediatric emergency department - Narule, Akash Vijay; Hirevenkanagoudar, Usha; M., Pranam G.; Chetty, Sanjeev (International Journal of Contemporary Pediatrics, 2025)
Background: In paediatric intensive care units (PICU), assessing the severity of illness in in children is crucial for effective resource allocation. There is critical need for reliable, easy to use tools in Emergency department to assess disease severity and predict outcome in paediatric patient. By using the TOPS (T-temperature, O-oxygen saturation, P-perfusion, S-sugar) score, we aim to identify a simple and effective tool for early risk stratification in critically ill paediatric patients. Methods: A hospital-based prospective observational study was conducted in the ED Navodaya Medical College, Raichur, over three months. A total of 140 children aged 1 month to 18 years presenting to ED were included. TOPS Score were calculated with score of 0 for normal value and 1 for abnormal value for each parameter. Results: Out of 140 children presenting to Emergency Department, TOPS score of 4 is associate with maximum risk of mortality 30%, while score of 2 and 3 has less mortality of 11.5% And 25% respectively. TOPS Score ≥ 2 shows poor outcome with sensitivity of TOPS Score 83% and specificity 34% .CRT is factor associated with maximum risk of mortality with Odds ratio of 5.762 (p <0.05). Conclusions: The TOPS score, which includes critical parameters such as temperature, oxygen saturation, perfusion, and blood sugar, presents a promising tool for assessing disease severity and predicting outcomes in paediatric emergency care. Its simplicity and practicality make it an attractive option for clinicians, allowing for quick and efficient evaluation of patients.